Strain patterns during tensile, compressive, and shear fatigue of human cortical bone and implications for bone biomechanics - Winwood, K.; Zioupos, Peter; Currey, John D.; Cotton, J. R.; Taylor, M. (Wiley, 2006)
It is a common theme in basic bone biomechanics and in biomechanical applications that much of the behavior can be determined and is dictated by the level of strain, whether this pertains to bone physiology, bone remodeling, osseoinduction, osseointegration, or the development of damage. The development of damage, demonstrated by stiffness loss measurements, has already been reported in detail in the literature. However, the systematic study of the development of “plastic” (residual) strains, which are associated with the inelastic mechanical behavior of bone tissue, has generally been overlooked. The present study compares the rates at which the elastic (ea) and plastic components (ep) of strain developed during tensile, compressive, and shear fatigue in human cortical bone of six individuals aged between 53 and 79 years. The overall hypothesis of this investigation is that there is a common underlying factor in the damage‐related behavior of bone, which may allow us to link together the various aspects of the damage related behavior of bone. The rate of development of plastic strain (Δep/ΔN) and the rate of growth in elastic strain amplitude (Δea/ΔN) are described as a function of the stress (σ), and/or stress normalized by the modulus of elasticity (σ/E). The implications of our findings are discussed with respect to simple models/mechanisms, which may underlie the observed behavior. © 2006 Wiley Periodicals, Inc. J Biomed Mater Res, 2006
Keywords: Cortical bone; Fatigue; inelastic strain